Planificación tributaria y su cumplimiento financiero en la empresa Comercializadora San Juan SAC, periodo 2022 - Arevalo Sias, Ivis Mayret (2023)
Tax planning is a management tool of vital importance for any company, because through it, management can plan not only the determination of taxes, but also their timely compliance, in such a way that an order can be established. and control in tax matters for your own benefit, avoiding infractions as well as excessive payment of taxes. The present investigation entitled "Tax planning and its financial compliance in the company Comercializadora San Juan SAC, period 2022", aims to determine the relationship between tax planning and its compliance in the aforementioned company in said period under study. Likewise, the research presented a methodology with a quantitative approach and a descriptive-correlational design. After having analyzed the data, it has been possible to determine that there is a significant relationship between tax planning and financial compliance, which has been demonstrated by the Rho Spearman correlation coefficient of 0.897 and its significance of 0.000.